Predictions for Sex of First Born Child Reflect Masculine and Feminine Characteristics in Male and Female Undergraduates. (1st October 2013) - Palmer-Hague, Jaime L.; Zilioli, Samuele; Watson, Neil V.
Previous research has identified physical and behavioral differences between parents who produce sons and those who produce daughters. However, the possibility that men and women have predictions about the sexes of their offspring based on these differences, or any other interoceptive cues, has not been investigated. We compared the dominance, sociosexual orientation, estradiol, testosterone, and 2D:4D ratios of men and women who predicted they would conceive a boy as their first child with those who predicted a girl. Women who predicted they would have a boy were more dominant and less sociosexually restricted than those who predicted they would have a girl. Men who predicted they would have a girl had higher salivary estradiol and higher (more feminine) 2D:4D ratios than those who predicted they would have a boy. Possible implications of these results are discussed in the context of evolutionary theory.